A combined oxygen and silicon diatom isotope record of Late Quaternary change in Lake El'gygytgyn, North East Siberia - Swann, George E.A.; Leng, Melanie J.; Juschus, Olaf; Melles, Martin; Brigham-Grette, Julie; Sloane, Hilary J. (Elsevier, 2010)
Determining the response of sites within the Arctic Circle to long-term climatic change remains an essential pre-requisite for assessing the susceptibility of these regions to future global warming and Arctic amplification. To date, existing records from North East Russia have demonstrated significant spatial variability across the region during the late Quaternary. Here we present diatom δ18O and δ30Si data from Lake El'gygytgyn, Russia, and suggest environmental changes that would have impacted across West Beringia from the Last Glacial Maximum to the modern day. In combination with other records, the results raise the potential for climatic teleconnections to exist between the region and sites in the North Atlantic. The presence of a series of 2-3‰ decreases in δ18Odiatom during both the last glacial and the Holocene indicates the sensitivity of the region to perturbations in the global climate system. Evidence of an unusually long Holocene thermal maximum from 11.4-7.6 ka BP is followed by a cooling trend through the remainder of the Holocene in response to changes in solar insolation. This is culminated over the last 900 years by a significant decrease in δ18Odiatom of 2.3‰, which may be related to a strengthening and easterly shift of the Aleutian Low in addition to possible changes in precipitation seasonality.